Scripting Fertility: Desire and Regeneration in Japanese North American Literature - Ty, Eleanor (Unfastened, 2010)
A number of Japanese North American novels have explored the traumatic experience of dislocation, internment, confiscation of property, and dispersals of the Japanese Canadian and Japanese American communities during and after the Second World War and the consequences of these events. The best - known example is Joy Kogawa’sObasan,which delineates the mostly silent suffering of Japanese Canadians during that period. Other works about Japanese Americans during the war include Monica Itoi Sone’sNisei Daughterand John Okada’sNo-No Boy.Recently Japanese Canadian and Japanese American novels have been moving away from focusing on that subject and have attempted